2020
DOI: 10.21203/rs.3.rs-58460/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regional and chronological differences in prevalences of olfactory and gustatory dysfunction in coronavirus disease (COVID-19): a systemic review and meta-analysis

Abstract: Olfactory and gustatory dysfunction are frequently reported in patients with coronavirus disease (COVID-19). However, the reported prevalence of olfactory and/or gustatory dysfunction varies widely, and the reason for the inter-study differences is unclear. Hence, in this meta-analysis, we performed subgroup analyses to investigate the factors that contribute to the inter-study variability in the prevalence of olfactory and gustatory dysfunction. Out of 943 citations, we included 55 eligible studies with 13,52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(29 citation statements)
references
References 22 publications
1
27
1
Order By: Relevance
“…Most studies are similar to those previously graded as "moderate risk of bias." 3,5,[10][11][12]14 Studies with high risk of bias (e.g., Bagheri et al, 2020 120 ) 14 were not included in our analysis, based on our inclusion criteria. Potential weaknesses are that measures mostly were not validated, 7 but it has to be considered that data were collected during an unprecedented pandemic and at a time when using more timeconsuming assessment tools often was not possible due to increased risk of virus spreading.…”
Section: Possibility Of Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies are similar to those previously graded as "moderate risk of bias." 3,5,[10][11][12]14 Studies with high risk of bias (e.g., Bagheri et al, 2020 120 ) 14 were not included in our analysis, based on our inclusion criteria. Potential weaknesses are that measures mostly were not validated, 7 but it has to be considered that data were collected during an unprecedented pandemic and at a time when using more timeconsuming assessment tools often was not possible due to increased risk of virus spreading.…”
Section: Possibility Of Biasmentioning
confidence: 99%
“…The findings of many of the earlier studies were compiled in 14 recent reviews. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Six of these reviews conducted a meta-analysis (of ten studies, 10 12 studies, 13 22 studies, 11 24 studies, 1 34 studies, 5 and 55 studies, 12 ), the other eight are narrative reviews. 2-4, 6-9, 14 Studies reported prevalence of chemosensory dysfunction with wide ranges, between 3% and 98% for anosmia, and between 6% and 93% for taste dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 Similarly, a suspected increase in SARS-CoV-2 infectivity and a faster interindividual spread outside of East Asia appears to be associated with an increase in the incidence of chemosensory dysfunction during the pandemic’s progression. 2 Finally, recent studies show that both the G614 variant and a more frequent occurrence of chemosensory deficits correlate with a higher viral load in the upper respiratory tract. 5 , 16 Although the above correlations require further experimental confirmation, they do support the scenario that the switch from D614 to G614 in the SARS-CoV-2 spike protein may contribute to the increase in prevalence of chemosensory dysfunctions in the COVID-19 pandemic.…”
Section: D614g Spike Variant As the First Putative Viral Factor Affecmentioning
confidence: 98%
“…Since the beginning of the pandemic, there has been a trend toward an increase in the incidence of chemosensory dysfunctions, especially between February and the end of March. 2 The latest and most extensive meta-analysis based on over 38 000 patients showed a statistically significant 3-fold higher prevalence of chemosensory dysfunction in Europe and America compared to Asia. 1 Multiple investigators have proposed that both viral and host genetic factors contribute to this phenomenon (reviewed by von Bartheld et al).…”
Section: Introductionmentioning
confidence: 99%